Pendidikan Seksual Komprehensif sebagai Kunci untuk Merubah Pandangan tentang Gender pada Siswa Sekolah Dasar - Novita Barokah; Nur Khasanah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research is motivated by a lack of knowledge about sexual education and gender issues in early childhood, especially elementary school (SD) students. Sexual education and gender issues are also topics that are currently still hotly discussed and continue to be an important concern in society. Many parents and local communities still consider sexual education to be taboo for young children, especially elementary school (SD) students. The aim of this research is to find out how to change students' views about gender through comprehensive sexual education, to find out sexual education learning methods, and to find out the role of teachers and parents in supporting the success of comprehensive sexual education. This research is based on literature study, namely a series of activities related to collecting library data, reading and taking notes, and processing research materials. The results of this research show that comprehensive sexual education can be a very important tool in changing elementary school students' views regarding gender by providing detailed and comprehensive information. Effective learning methods in teaching comprehensive sexual education are lecture, discussion and question and answer methods. The role of parents in supporting the success of comprehensive sexual education is that parents are ready to provide sexual education to their children, providing role models and guidance, accepting questions from children and providing appropriate responses, emphasizing always respecting privacy. Meanwhile, the role of teachers includes as instructor, guide, mediator and evaluator.